2015
DOI: 10.1080/08989621.2015.1047707
|View full text |Cite
|
Sign up to set email alerts
|

Authorship Issues and Conflict in the U.S. Academic Chemical Community

Abstract: A survey on credit issues and related “responsible conduct of research” (RCR) behaviors was conducted with academic chemists in Ph.D. granting institutions in the U.S. Six hundred faculty members responded. Fifty percent of the respondents reported not receiving appropriate credit for contributions they had made to projects the results of which had been published, including when they themselves were students. Thirty percent of these individuals discussed this lack of credit with the “offending” individual, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 62 publications
(92 reference statements)
0
20
0
Order By: Relevance
“…Thus, conducting educational activities that aim to encourage, clarify and demystify the article writing can be an essential and effective strategy for publication and, consequently, reduce mental distress and exhaustion of the graduate student. (11,22) In a study performed in an Australian university nursing school,, it was reported that the implementation of a strategic plan to engage students and educators was essential to motivate the production of scientific papers. During 20 months, there were workshops on practical aspects of publication, scientific writing, presentation process and paper format, using search engines, where to publish, and other topics relevant to publication.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, conducting educational activities that aim to encourage, clarify and demystify the article writing can be an essential and effective strategy for publication and, consequently, reduce mental distress and exhaustion of the graduate student. (11,22) In a study performed in an Australian university nursing school,, it was reported that the implementation of a strategic plan to engage students and educators was essential to motivate the production of scientific papers. During 20 months, there were workshops on practical aspects of publication, scientific writing, presentation process and paper format, using search engines, where to publish, and other topics relevant to publication.…”
Section: Discussionmentioning
confidence: 99%
“…These work-shops were conducted by editors of academic journals and experienced researchers, and resulted in an improvement of participants' skills. (22) In addition, considering the reality worldwide, (11,22) there are aspects related to difficulty and the obligation to publish, which may cause tension in graduate students, such as uncertainty about paper acceptance, the contributions and criticism of reviewers, and the publication costs, among others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in collaborative studies, each person's relative contribution is difficult for the research team to determine and for others to understand [23]. As a result, authorship disputes remain a troublesome issue [19,[24][25][26][27].…”
Section: Authors Contributors and Acknowledgeesmentioning
confidence: 99%
“…Striving to compete is sometimes accompanied with many biases introduced into the body of scientific knowledge alongside its production's path from the attribution of funds to the final phase of publication and citation. Citation biases are one of many other problems in a broader context of unethical practices affecting science and scientific publications, such as authorship issues (Seeman and House 2015) (Seeman and House 2010) (Bennett and Taylor 2003), redundant or duplicate publications (Abraham 2000) (Hennessey et al 2012) (de Vasconcelos and Roig 2015), hyper-authorship (Cronin 2001), bias in editorial decisions (Kotchoubey et al 2015) , and in ethical decision making among university faculty (Medeiros et al 2014), plagiarism (Resnik 2013) (Bird 2002), guest and ghost authorship (Wislar et al 2011) (Ngai et al 2005), research misconducts (Resnik et al 2015) (Spier and Bird 2000) and many other contradictions and pitfalls (Moustafa 2014).…”
Section: Introductionmentioning
confidence: 99%